Sovereign debt sustainability in MENA countries: Determinants and policy implications - Kais Ben Mbarek (Modern Finance)
This paper examines sovereign debt sustainability in the Middle East and North Africa (MENA) region by comprehensively analyzing macroeconomic, institutional, and geopolitical determinants. Using a panel dataset of 15 MENA countries spanning 2000-2023, we employ dynamic panel estimation techniques to identify key factors affecting debt sustainability. Our findings reveal significant heterogeneity across the region, with oil-exporting countries demonstrating distinct debt dynamics compared to oil-importing nations. Institutional quality and governance indicators emerge as critical predictors of debt sustainability beyond traditional macroeconomic variables. Furthermore, our threshold analysis identifies specific debt-to-GDP levels at which growth effects become negative, varying substantially across country groups. The results underscore the importance of tailored policy approaches to regional debt management, challenging one-size-fits-all recommendations from international financial institutions. This research contributes to the literature by developing a novel composite debt sustainability index and providing empirical evidence on the region-specific determinants of sustainable sovereign debt management.